Congenital Knee Dislocation: Help for Neonatologists and Pediatricians - Igor Yu. Kruglov; Nicolai Yu. Rumyantsev; Gamzat G. Omarov; Natalia N. Rumyantseva; Ilya M. Kagantsov (Вопросы современной педиатрии)
Congenital knee dislocation is relatively rare pathology of the musculoskeletal system. Timely diagnosis and treatment onset allow us to achieve full range of motion in the knee joint. However, low awareness of physicians in these topics and, as a result, diagnostic errors lead to pseudo-correction and motor deficit in the knee joint. This article describes correct examination of a child with congenital knee dislocation directly in the delivery room, management after discharge, and subsequent patient's routing with the assistance of orthopedic traumatologist.